Zakat Accountability Optimization (Study on the National Amil Zakat Agency, Grobogan Regency, Central Java) - Ilahi, Viliana Nanda; Satibi, Ibi (Journal of Accounting Inquiry, 2023)
Purpose: This study aims to describe zakat management from the point of view of optimizing zakat accountability. Methodology: The object of this study is the Badan Amil Zakat Nasional (BAZNAS) Grobogan District with informants from the Organizers of Zakat and Waqf District Department of Religion Grobogan, BAZNAS Grobogan District, muzaki, and mustahik who live in the Grobogan District. This study uses a qualitative approach. Data collection techniques include interviews, observation, and documentation. The results of the data study are more regarding the interpretation of the data found in the field. Findings: Research results show that BAZNAS Grobogan District has fulfilled elements of optimizing zakat accountability. However, the accountability of zakat on BAZNAS still needs to be optimal in terms of performance and finance. Three factors support the optimization of BAZNAS zakat accountability: socialization and coordination of effective institutional, good coordination with other institutional zakat managers, and strengthening human resources through additions and institutional capacity training. Three-factor inhibitor optimization of BAZNAS zakat accountability, namely performance and administration of SOPs not yet functional, HR in the fields and IT need to be more adequate, and the collection of zakat needs to support Regional Regulations fully. Novelty: This study finds its novelty in locus, time, methodology, and variables. Locus from study This is BAZNAS Grobogan District as the object. This is because there has yet to be research at BAZNAS Grobogan District. Qualitatively study This critic.   Keywords: Optimization, Management, Accountability, Zakat, BAZNAS